Income Tax Calculation and Deposit Analysis - Ikhtiari, Kirana (Advances in Applied Accounting Research, 2023)
The purpose of this study was to determine whether the calculation of income tax article 22 on the procurement of goods at the Education Office of Tana Toraja Regency has been carried out properly in accordance with the Regulation of the Minister of Finance Number 154/PMK.03/2010 and to determine whether the payment of income tax article 22 on procurement goods at the Tana Toraja Regency Education Office have been carried out properly in accordance with the Minister of Finance Regulation Number 242/PMK.03/2014. This research method is descriptive qualitative and quantitative descriptive by using interview and documentation method. Data analysis using Descriptive Analysis. The results of the study found that: (1) the calculation of income tax article 22 on the procurement of goods at the Education Office of Tana Toraja Regency has been carried out properly in accordance with the Regulation of the Minister of Finance Number 154/PMK.03/2010; and (2) the payment of income tax article 22 on the procurement of goods at the Education Office of Tana Toraja Regency has been carried out properly in accordance with the Regulation of the Minister of Finance Number 242/PMK.03/2014.